Quality By design na indústria farmacêutica - Cintra, João Vítor França da Rosa Ferreira (Universidade Federal de São Carlos, 2024)
This work synthesizes the Quality by Design (QbD) approach in the context of pharmaceutical production. The beginning of the research focuses on the essence of QbD, highlighting its innovative application in drug development. The initial emphasis is on the identification and control of Critical Material Attributes (CMA's) and Critical Process Parameters (CPP's), essential elements to ensure product quality from the early stages of the process to large-scale production. The research comprehensively addresses risk assessment techniques, providing an understanding of how these factors impact the performance of production processes. A practical case study in the pharmaceutical industry, using the generic drug Acetriptan 20 mg, is presented in the research. Through this example, acceptable ranges are demonstrated, showing how the attributes of input materials and process parameters influence the quality of the intermediate and final product, allowing for the efficient identification and control of critical factors throughout the production cycle. The central tool of QbD, Design of Experiments (DoE), is demonstrated across different stages, including screening, optimization, and process robustness evaluation. The research uses the practical example of Acetriptan formulation development to highlight how DoE contributes to the identification of optimal conditions, critical and non-significant factors, as well as interactions between variables. The Design Space (DS) is presented as a desirable element of QbD, providing a clear understanding of variables and ranges to ensure consistent and quality production. Graphic examples, such as contour plots and three-dimensional graphs, are discussed as effective means of representing the DS. Additionally, the need for a comprehensive regulatory presentation when submitting a DS to the FDA is demonstrated, including a clear description, variable interactions, justification data, and the relationship with unit operations. The work offers a comprehensive analysis of QbD in the pharmaceutical industry, demonstrating its practical application, key tools, and relevance in ensuring quality and consistency in pharmaceutical production.
Quality By design in the pharmaceutical industry
Keywords: Qualidade por concepção; Produção farmacêutica; Delineamento experimental; Pharmaceutical production; Design of experiments; Quality by design; CIENCIAS DA SAUDE::FARMACIA::ANALISE E CONTROLE E MEDICAMENTOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE